Mortality and causes of death among incident cases of systemic lupus erythematosus in Finland 2000–2008. (November 2014) - Elfving, P; Puolakka, K; Kautiainen, H; Virta, L J; Pohjolainen, T; Kaipiainen-Seppänen, O
The objectives of the study were to investigate mortality and causes of death in patients with recent-onset systemic lupus erythematosus (SLE) in Finland. Data for patients with SLE for the study were collected (2000–2007) from the nationwide register on decisions of special reimbursements for drugs, maintained by the Social Insurance Institution (SII) in Finland. Data on deaths of the patients were obtained from the official death certificate statistics of Statistics Finland until the end of 2008. Of the 566 incident SLE patients, median follow-up time was 5.4 (IQR 3.3, 7.1) years, and 30 patients (23 females, seven males) died in the years 2000 through 2008. Mean age at death was 67.8 ± 17.2 years for females and 62.3 ± 15.2 years for males. The 5-year survival rates were 94.8% (95%CI 92.0–96.6%) and 88.2% (95%CI 76.5–94.3%), respectively. The age- and sex-adjusted standardized mortality ratio was 1.48 (95%CI 1.01–2.12). Primary causes of death were cardiovascular diseases, malignancy and SLE itself. In conclusion, survival of the patients with SLE was inferior to that of the general population. Cardiovascular diseases were responsible for 37% of deaths.